German Male Income Volatility 1984 to 2008: Trends in Permanent and Transitory Income Components and the Role of the Welfare State - Charlotte Bartels; Timm Bönke (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Deploying data from the German Socio-Economic Panel (SOEP) we analyze the variability of individual earnings and equivalent household income. Permanent and transitory variances of male income over the period 1984-2008 are estimated for Old German Laender in order to determine their importance to income dynamics. To uncover the role of the welfare state in smoothening earnings shocks we compute different income concepts reaching from gross earnings to net equivalent household income. We find evidence that the overall inequality of earnings in Germany has been rising throughout the period due to both higher permanent inequality and higher volatility. However, taking the welfare state and its institutions into account, we find that net household income has remained fairly stable.
Keywords: D31; D63; I38; J31; 330; Earnings inequality; permanent income inequality; transitory income volatility; earnings dynamics; safety net; transfer payments; Einkommen; Volatilität; Öffentliche Sozialleistungen; Haushaltseinkommen; Verfügbares Einkommen; Männliche Arbeitskräfte; Schätzung; Deutschland